“I AM TIRED” – Job Burnout and Citizenship Behaviour in an Organization: Occupational Commitment as a Mediator in a Malaysian Private University - Chen, I-Chi; Peng, Ng Lee; Ann, Chong Chin (International Dialogues on Education Journal, 2020)
Today, academics are under high pressure to equip themselves to satisfy various demands. The aim of this study is to investigate the relationship between job burnout, occupational commitment, and organizational citizenship behaviour (OCB) among academics at a private university in Malaysia. The present study was applied on the basis of PLS-SEM analysis. A total of 620 academics from two campuses of a private university participated in the study. The results indicate that emotional exhaustion is the most stressful indicator of job burnout. Secondly, job burnout was found to exert a significant negative influence on OCB as well as occupational commitment. Finally, occupational commitment was found to be a mediator between job burnout and OCB. In summary, this study aims to improve the professional commitment and OCB of academic staff by addressing job burnout.